Beckwith–Wiedemann and Silver–Russell syndromes: opposite developmental imbalances in imprinted regulators of placental function and embryonic growth. (9th April 2013) - Jacob, KJ; Robinson, WP; Lefebvre, L
Abstract : Beckwith–Wiedemann syndrome (BWS) and Silver–Russell syndrome (SRS) are two congenital disorders with opposite outcomes on fetal growth, overgrowth and growth restriction, respectively. Although both disorders are heterogeneous, most cases of BWS and SRS are associated with opposite epigenetic or genetic abnormalities on 11p15.5 leading to opposite imbalances in the expression levels of imprinted genes. In this article, we review evidence implicating these genes in the developmental regulation of embryonic growth and placental function in mouse models. The emerging picture suggests that both SRS and BWS can be caused by the simultaneous and opposite deregulation of two groups of imprinted genes on 11p15.5. A detailed description of the phenotypic abnormalities associated with each syndrome must take into consideration the developmental functions of each gene involved. Abstract : Section Editors: Jacques L. Michaud, e‐mail:jacques.michaud@recherche-ste-justine.qc.ca Olivier Pourquié, e‐mail:pourquie@igbmc.fr